2018
DOI: 10.1159/000494099
|View full text |Cite
|
Sign up to set email alerts
|

A Radiomics Nomogram for Preoperative Prediction of Microvascular Invasion in Hepatocellular Carcinoma

Abstract: <b><i>Background:</i></b> Radiomics has emerged as a new approach that can help identify imaging information associated with tumor pathophysiology. We developed and validated a radiomics nomogram for preoperative prediction of microvascular invasion (MVI) in hepatocellular carcinoma (HCC). <b><i>Methods:</i></b> Two hundred and eight patients with pathologically confirmed HCC (training cohort: <i>n</i> = 146; validation cohort: <i>n</i> = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
240
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 253 publications
(264 citation statements)
references
References 41 publications
19
240
2
3
Order By: Relevance
“…Extensive studies have shown that radiomics have great potential in predicting tumor biology and in improving implementation of precision medicine (18,23,28,29). Previously, some studies have established radiomic signatures for detecting the presence of MVI based on CT and MRI (11)(12)(13)(14). Radiomic signatures based on arterial phase and delay phase of contrast-enhanced CT have yielded AUCs of 0.684 and 0.490, respectively (11).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Extensive studies have shown that radiomics have great potential in predicting tumor biology and in improving implementation of precision medicine (18,23,28,29). Previously, some studies have established radiomic signatures for detecting the presence of MVI based on CT and MRI (11)(12)(13)(14). Radiomic signatures based on arterial phase and delay phase of contrast-enhanced CT have yielded AUCs of 0.684 and 0.490, respectively (11).…”
Section: Discussionmentioning
confidence: 99%
“…Radiomic signatures based on arterial phase and delay phase of contrast-enhanced CT have yielded AUCs of 0.684 and 0.490, respectively (11). Additionally, radiomic signatures based on hepatobiliary-phase T1-weighted MRI have yielded an AUC of 0.705 in predicting MVI (14). A recent study incorporating clinical risk factors into ultrasound radiomic scores yielded efficacious performance in MVI prediction, with an AUC of 0.731 (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations